Соціальна функція сучасної держави у контексті розвитку основоположних принципів права - Данич, О.Ф. (Альманах права, 2012)
Автор статті аналізує вплив права на формування держави та функціонування основних функцій держави, необхідність правового обґрунтування ролі і місця держави у формуванні соціальної політки, узгодження механізмів державно-правового регулювання всіх сфер життєдіяльності суспільства й механізмів ринкового саморегулювання. Автор статьи анализирует влияние права на формирование государства и функционирование основных функций государства, необходимость правового обоснования роли и места государства в формировании социальной политики, согласование механизмов государственно-правового регулирования всех сфер жизнедеятельности общества и механизмов рыночного саморегулирования. The article examines the legal nature of the state functioning, the state’s role in shaping social policy, the need for legal justification for the role and place of the state in shaping social policy issues, role of society and the state in shaping the social state of law in Ukraine. It considers social function of the state in the context of the fundamental principles of law and the impact of law onto state formation and functioning of the basic state functions. It also concerns coordination of public-law regulation of all spheres of society and the mechanisms of market self-regulation. It acknowledges the need of the social evolution of the state and focused state and legal impact on the functioning and development of public relations.